Atherothrombosis‐on‐Chip: A Site‐Specific Microfluidic Model for Thrombus Formation and Drug Discovery (Adv. Biology 7/2022). Issue 7 (15th July 2022) - Akther, Fahima; Zhang, Jun; Tran, Huong D. N.; Fallahi, Hedieh; Adelnia, Hossein; Phan, Hoang‐Phuong; Nguyen, Nam‐Trung; Ta, Hang Thu
Abstract : Atherothrombosis‐on‐Chip In article 2101316, Ta and co‐workers conducted a study to mimic the site‐specific atherothrombosis formation on the chip and design a unique microfluidic device with two interconnected microchannels. The device allows the site‐specific introduction of plaque components to develop localized thrombosis and provides a universal platform for studying the crosstalk between blood cells and plaque components. The device is expected to benefit drug testing and carrier designing.